669 Is Outpatient Spine Surgery at an Ambulatory Surgical Center Better Than at a Hospital? A MSSIC Study. (April 2023) - Hamilton, Travis Matthew; Mansour, Tarek R.; Hadi, Moustafa; Deshpande, Nachiket; Shultz, Lonni; Springer, Kylie; Hu, Jianhui; Nerenz, David; Zakko, Philip; Khalil, Jad; Park, Daniel; Easton, Richard; et al.
Abstract : INTRODUCTION: The number of outpatient surgeries have quadrupled over the past several decades. Although studies have shown increased efficacy and cost-effectiveness of surgery done in an outpatient setting, few studies have compared outpatient surgeries performed at a hospital versus an ambulatory surgery facility (ASF) METHODS: The Michigan Spine Surgery Improvement Collaborative was queried for patients undergoing cervical and/or lumbar spine surgery between 1/1/2021 to 12/31/2021 performed at an ASF or hospital with same day discharge. A 4-to-1 propensity score matching using BMI, location (lumbar, cervical), ASA > 2, fusion procedure and number of levels as the matching variables for lumbar and cervical surgeries. Primary outcomes included: achieving MCID for PROMIS physical function, EQ-5D, Return-to-Work and NASS patient satisfaction. Complications were a secondary outcome and included: Surgical site Infection (SSI), urinary retention, hospital readmission/ED visit, return-to-OR, Axial pain, new radicular findings, weakness, Ileus (lumbar only), and Dysphagia (cervical only). RESULTS: A total of 2, 763 patients were identified prior to matching. Of the 1, 665 patients that were matched, 1, 332 had surgery at a hospital and 333 in an ASF. There were no statistically significant differences for patient satisfaction, PROMIS-PF MCID, or Return-to-Work at 90-days. Patients who had surgery at an ASF had higher rates of axial pain (10% vs 5%, p = 0.002) and new radicular findings(19% vs 12%, p < .001) compared to surgery at a hospital. Dysphagia was also higher in the ASF group (5% vs 0%, p = .006). There were no differences in SSI, readmission, urinary retention, return-to-OR or ED visits between sites CONCLUSIONS: Outpatient spine surgery at an ASF demonstrated no significantly increased surgical morbidity compared to hospitals. Although ASFs had a higher rate of new radicular findings and axial pain, there were no differences in patient satisfaction and PROs after surgery.